Abbott & Costello. The complete Universal Pictures collection. [Discs 13-15] [videorecording (DVD)] - Lamont, Charles, 1895-1993; Abbott, Bud, 1897-1974; Costello, Lou; Blanchard, Mari; Paige, Robert, 1910-1987; MacMahon, Horace, 1907-1971; Karloff, Boris, 1887-1969; Westcott, Helen, 1928-1998; Stevens, Craig, 1918-2000; Seinfeld, Jerry (Universal Studios Home Entertainment, 2008)
Abbott and Costello go to Mars: Bud and Lou accidentally take off for Mars and end up in New Orleans during Mardi Gras. Abbott and Costello meet Dr. Jekyll and Mr. Hyde: As American policemen in London, Bud and Lou meet up with Dr. Jekyll and Mr. Hyde. Abbott and Costello meet the Keystone Kops: Bud and Lou follow a con man to Hollywood after being swindled into buying a phony movie studio. Abbott and Costello meet the Mummy: Bud and Lou stumble upon a sacred medallion that holds the key to a legendary treasure. On disc 15, laugh out loud with the most popular comedy duo of all time. Featuring Bud and Lou's most popular movies, this collection is filled with some of the most hilarious routines of all-time.